Mini-Review: Heat Transfer Mechanisms in MILD Combustion Systems - Ceriello, Giuseppe; Sorrentino, Giancarlo; Cavaliere, Antonio; de Joannon, Mara; Ragucci, Raffaele (Frontiers in Mechanical Engineering, 2021)
MILD combustion has a wide potential in enhancing thermal efficiency with nearly zero emissions. It has no visible flame since the radiation from the reacting zones is attenuated due to both the intermediate species at reduced temperatures, induced by intensely burned gas recirculation, and the absence of particulate emitters. Beyond these main features, there are other characteristics such as temperature uniformity and distributed ignition that have to be addressed and analyzed looking at the peculiar role of the heat transfer for such reactors. First, the category of combustion systems object of the study is described. Afterwards an analysis on the heat transfer mechanisms under MILD combustion of gaseous fuels is carried out. Therefore, in this Mini-Review, several literature findings highlighting the role of the heat transfer on the combustion peculiarities of MILD reactors (i.e., temperature uniformity, distributed ignition, low pollutant emissions) are reported and discussed. Heat exchange modes, in fact, contribute to providing MILD macroscopic characteristics by means of the strong interplay between wall and gas heat transfer, instead of the reactive structure. In particular, the thermal behavior of these systems is analyzed in order to stress the distinctive role of the heat loss and the relative contributions of the convective and radiative terms. Heat transfer mechanisms between gas and walls and their interactions, in fact, favor the wide temperature distribution within the chamber. In order to better understand the different effects of the heat transfer under MILD regime, the mechanisms regarding walls and recirculating gas are separately investigated.